PERANCANGAN APLIKASI CUSTOMER RELATIONSHIP MANAGEMENT BERBASIS WEB PADA PT. BANK INTERNASIONAL INDONESIA CABANG PONTIANAK - Hasan . (STMIK PONTIANAK, 2013)
Abstract:Design of Customer Relationship Management Web-Base Application for PT Bank Internasional Indonesia, Tbk. branch of Pontianak. This study aims to to develop an CRM application to provide the best services to their customers, and than to ccommodate some complaints from the customers, and manage relationships with customers in order that the customer loyalty is remains awake and does not switch to another bank. Designing CRM begins with identifying the needs of the system, and than created the system design with UML diagrams. The result is an web-based application of CRM that has the facility to manage customer data, banking product display, and display the frequently ask questions FAQ). It also includes complete customers personal data which includes date of birth, hobbies and habits of the customer must be clearly understood by the CSO or relationship officer to support services exclusively to customers who have given a major contribution to the BII branch of Pontianak. Keywords: customer relationship management, web-based application, customer services